Prognostic Value of Pre- and Posttreatment PET/CT Parameters in Patients Diagnosed with Advanced Stage NSCLC - Bilir, Cemil; Yusufoglu, Baran; Kizilkaya, Bayram; Engin, Huseyin (Current Medical Imaging, 2018)
Background: PET imaging involves several parameters. However, it is not well known which parameters in each measurable site of tumors may have a greater effect on oncologic outcomes. Method: This study included a total of 42 patients diagnosed with histology-proven NSCLC. Baseline and consecutive FDG-PET scans were carried out 3 weeks before and at least 3 months after treatment, respectively. Results: According to the PERCIST, 9 (21%) patients had Complete Response (CR), and 3 of them underwent surgical resection. Sixteen patients (38%) had Partial Response (PR), and 4 (9.5%) had Stable Disease (SD), the remaining 15 (35%) had Progressive Disease (PD). Patients who responded to the treatment had significantly higher Overall Survival (OS) and Progression Free Survival (PFS), 15 versus 9.5 months and 10 versus 6 months, respectively. The SUVmax values decreased from 12.2 to 3.7 (P=<0.001), and the mediastinal lymph nodes SUVmax decreased from 6 to 0 (P=<0.001) in the responder group. The median TLG of the primary lesion showed a statistically significant decrease from 279 to 13.6 (P=0.0001), the median TLG of the mediastinal lymph nodes decreased from 13.2 to 0 (P= 0.04), and the median Whole Body (WB) TLG decreased from 338 to 17 (P=0.002) in the responder group. The posttreatment WB TLG was significantly correlated with OS and PFS. Conclusion: This study showed that the posttreatment WB TLG is significantly associated with oncologic outcomes. The metabolic changes in the mediastinal lymph nodes, as shown by the SUVmax and TLG, have a prognostic value in patients who develop new metastases during treatment. Further study in a homogenous NSCLC population can help increase our understanding of the prognostic value of PET/CT parameters.
Keywords: survival